INTRODUCTION TO SCIENCE THROUGH EXPERIMENTAL SCIENCE EXPERIMENTS TO IMPROVE EARLY CHILDHOOD COGNITIVE ABILITIES - Ashilah Zahra; Aisyahtul Amira; Rizkia Hafidzah; Jamia Muddin; Kurniati Yahya (Universitas Panca Sakti Bekasi, 2024)
Experimental Experiments is a learning method that is very popular with early childhood, therefore this method is very effective to improve early childhood cognitive abilities as a provision for continuing education to the next level. This study aims to improve cognitive abilities through hot air balloon experiments at TKIT Ummul Quro Manokwari in 2024. This research is a Classroom Action Research (PTK) which is carried out using two cycles. The subjects of this study were group B aged 5-6 years with a total of 20 people, 9 men and 11 women. Data analysis techniques in this class action research use descriptive statistical analysis techniques. By using observation instruments as a data collection tool. The results of the data that have been analyzed are that in cycle 1 the child's cognitive ability reaches MB (Starting to Develop), while in the 2nd cycle the increase in children's cognitive ability reaches BSH (Develop as expected). So that the increase in children's cognitive abilities from cycle 1 to cycle 2 has progressed quite well.